Say something back - Riley, Denise 1948- (NYRB Poets, 2020)
"A moving meditation on grief and motherhood by one of Britain's most celebrated poets. Say Something Back will allow readers to see just why Denise Riley has been held in such high regard by her fellow poets for so long. The book reproduces A Part Song, a profoundly moving document of grieving and loss, and one of the most widely admired long poems of recent years. Elsewhere these poems become a space for contemplation of the natural world and of physical law, and for considering what it is to invoke those who are absent. But finally, they extend our sense of what the act of human speech can mean--and especially what is drawn forth from us when we address our dead. Lyric, intimate, acidly witty, unflinchingly brave, Say Something Back--which also includes a powerful new prose meditation about grief and its aftermath, "Time Lived, Without Its Flow"--is a deeply moving book by one of our finest poets, and one destined to introduce Riley's name to a wide new readership"--
Keywords: Parental grief / Poetry; Bereavement / Poetry; Death / Poetry; Children / Death / Poetry; Bereavement; Children / Death; Death; Parental grief; Poetry